IS THE PAYMENT ACCORDING TO THE DIAGNOSIS COMPARABLE WITH THE REAL COST OF TREATMENTS? - PEVEC, TEODOR optional (PONS - medicinski časopis, 2014)
ABSTRACT Introduction: The model of DRG (Diagnosis Related Groups) is the currant method of paying the health-care services. It is based on the principle dividing the patients into groups and using the similar quantity of sources. The treatment costs of a single case is determined by the weight of DRG and the cost of a weight. We both are interested, if our treatment costs of a single DRG case are within the values of DRG determined by the payer. Methods: At the department  we have chosen four frequent treatments, namely, observation of a patient having a brain concussion with a fissured wound on the head and being acute alcoholically intoxicated, then the treatment of a patient with appendicitis acuta, a patient with a hip fracture and a patient who was operated for inguinal hernia. We made the cost analysis and compared it with the payment that, for such cases, the hospital gets from its financier. Results: The costs of observation cases amounted, according to the DRG, to 422, 1474, 3865 and 894 EUR, and, according to cases they amounted to 502, 1105, 1881 and 544 EUR. Conclusion: The method of measuring the according to a case is the basic tool in the analysis of cost reduction, it submits measures at those points where saving money is possible. It also enables to supervise the cost efficiency of each individual physician.